IMPLEMENTASI KURIKULUM CAMBRIDGE DI SDI KREATIF MUTIARA ANAK SHOLEH SUKODONO SIDOARJO - Serifah Dini Fitria; Gatot Sujono; Mauhibur Rokhman (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
This article aims to describe and analyze the implementation of the Cambridge curriculum at the MAS Creative Islamic Elementary School. This type of research is descriptive qualitative research. This study used purposive sampling, where the sample of this study consisted of principals, vice-principals of the curriculum section, and teachers at SDI Kreatif MAS. Researchers used data collection techniques through observation, interviews, and documentation. The results of this study are the implementation of the Cambridge curriculum at SDI Kreatif MAS is said to be feasible and becomes one of the role models in the surrounding area as a school that implements an international curriculum. In stages, the Cambridge curriculum consists of three stages, namely 1) Planning, 2) Implementation, and 3) Evaluation. The advantages of the Cambridge curriculum are that students' thinking styles are much higher than students who only study the national curriculum, while the weakness is that there are still many who do not understand the sentence structure of each English-based reading due to the lack of application of English communication in the student's family environment.